Pengaruh Pupuk Organik dan Anorganik Terhadap Sifat Kimia Tanah pada Perkebunan - Panjaitan, Rio Mas Parmonangan; Parangin-angin, Junael Delviero; Syahputra, Denny Armawan; Saragih, Hanna Desporina Br; Simbolon, Rizky Aryandi; Pratama, Jovi; Pulungan, Muhammad Amin; Ginting, Makhrani Sari; M, Maisarah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Sustainable agriculture and plantations are at the heart of efforts to address global challenges related to soil sustainability and productivity. One important aspect in increasing soil productivity is the use of fertilizers. This article examines the effects of organic and inorganic fertilizers on soil chemical properties, with the aim of gaining an understanding of the effects of organic and inorganic fertilizers on soil fertility. Organic fertilizers such as manure have the advantage of increasing the organic matter content in the soil. Increasing organic matter increases the cation exchange capacity of the soil, improves soil structure and increases water holding capacity. This makes the soil more fertile and better able to support plant growth. In contrast, inorganic fertilizers such as urea directly supply essential nutrients to plants. Nitrogen, phosphorus and potassium contained in inorganic fertilizers rapidly increase plant growth. However, excessive use of inorganic fertilizers can increase soil acidity and disrupt the balance of soil nutrients. This article also discusses the importance of using a combination of organic and inorganic fertilizers. The combination of the two produces a positive synergistic effect where organic fertilizers increase nutrient retention from inorganic fertilizers and vice versa. Therefore, the integration of the two can provide optimal long-term benefits for the soil. By better understanding the impact of these fertilizers, we can develop more effective strategies to sustainably improve soil fertility.